Kemampuan Membaca Teks Laporan Hasil Observasi Siswa Kelas VII SMP Negeri 3 Rejang Lebong - Debby Lorensa Febuana; Dian Eka Chandra Wardhana; Gumono Gumono (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
The purpose of this study was to describe the reading ability of class VII students of SMPN 3 Rejang Lebong. This research method is a quantitative descriptive method. The population in this study were class VII SMPN 3 Rejang Lebong with the research sample being class VII E and VII H which were taken by random sampling. Data collection technique is done by testing technique. Students are tested with objective questions in the form of 4 discourses and each discourse consists of 3-6 questions. The results showed that the reading ability of class VII students of SMPN 3 Rejang Lebong regarding the text of the observation report was seen from several aspects, namely the structural aspect obtained an average value of 96.4 classified as very good criteria, aspects of linguistic elements obtained an average value of 72 including good criteria , aspects of the main idea of paragraphs obtained an average value of 72 including good criteria, aspects of the conclusion of paragraphs obtained an average value of 70.5 including good criteria, and aspects of analysis obtained an average value of 78 including good criteria. Overall, the aspect of students' reading ability with an average score is good, between 70-79% and each student has a different understanding of texts one to four.